EKSPRESI THUMOS MISHIMA YUKIO DALAM NOVEL KINKAKUJI - Zaki Ainul Fadli (Universitas Diponegoro, 2014)
In the social study, there is a concept about strong desire to be recognized by others named thumos. Mishima as a Japanese ultranasionalist have a value about guarding the traditional Japanese values. Among of these values is the absolute position of Japanese emperor in the state. If Mishima’s thumos which expressed in the novel linked with his ideology, there is strong similarity between the protagonist’s disappointment and Mishima’s critics related with the Japanese society. Those assumptions supported by novel’s structural aspects.